Platelet Aggregation Caused by Dithiothreitol - Zucker, M B; Masiello, N C (Thrombosis and Haemostasis, 1984)
MacIntyre et al. showed that over 1 mM dithiothreitol (DTT) aggregates blood platelets in the presence of fibrinogen; aggregation is not inhibited by prostaglandin E1. We confirmed their data and found that 70 mM 2-mercaptoethanol was also active. DTT- induced aggregation was not associated with platelet shape change or secretion of dense granule contents, was not inhibited by tetracaine or metabolic inhibitors, was prevented at pH 6.5, and prevented, reversed, or arrested by EDTA, depending on when the EDTA was added. DTT did not cause aggregation of thrombasthenic, EDTA-treated, or cold (0° C) platelets, which also failed to aggregate with ADP. Platelets stimulated with DTT bound 125I-labeled fibrinogen. Thus DTT appears to “expose” the fibrinogen receptors. SDS gel electrophoresis of platelet fractions prepared by use of Triton X-114 showed that aggregating concentrations of DTT reduced proteins of apparent Mr 69,000 and 52,000 (probably platelet albumin) and, to a variable extent, glycoproteins Ib, IIb and III. Exposure of unlabeled or 125I- labeled platelets to ADP had no discernible effect on the electrophoretic patterns.
Keywords: Platelet aggregation; Dithiothreitol; Fibrinogen receptors